PENGARUH LIKUIDITAS, CAPITAL, PROFITABILITAS TERHADAP TINGKAT SUKU BUNGA DEPOSITO BERJANGKA (Students' Journal of Accounting and Banking, 2013)
This study aims to analyze the effect of Liquidity ratio, Capital ratio, and Profitability ratio affects the Interest Rate On Fixed Deposit Banking Companies listed on the Stock Exchange. The population in this study are the financial statements of banking companies in Indonesia, published by the Stock Exchange during the period 2008-2011. The technique of collecting samples in this study using purposive sampling method which samples are taken based on the criteria used by the researchers. Samples taken as many as 21 commercial banks in 2008-2011.Testing the hypothesis in this study using multiple linear regression analysis. The results of this study is the coefficient of LDR and CAR showed a positive direction, so that it will raise the deposit interest rate setting, and the coefficient of ROA showed negative direction means an increase in ROA will decrease the deposit interest rate setting. From this study it can be concluded that based on the results of statistical tests that LDR variables have a positive significant effect on the determination of deposit rates, variable CAR no significant effect on the determination of deposit rates and the variable ROA is negative and significant effect on the determination of deposit rates.Keywords: Pengaruh Likwiditas , capital, profitabilitas, terhadap tingkat suku bunga deposito berjangka